The effect of combined thermal and sonication treatment on shelf life extension and quality retention of banana - Mahfujul Alam; Mir Meahadi Hasan; Mohammad Mainuddin Molla; Mrinal Kanti Debnath; Md Shakir Moazzem; Biddut Chandra Dey (Applied Food Research)
The banana is categorized as a climacteric fruit, exhibiting a high susceptibility to decay and a limited duration for consumption after being harvested. The aim of this present study was to assess the impactthermal and sonication treatments on the physiological quality parameters and microbial load of banana fruits. On the 12th day of storage, the untreated bananas exhibited the highest weight loss percentage (21.44 ± 1.55 %) and decay incidence (100 ± 0 %). In contrast, the bananas treated with a combination of hot water (HW) and ultrasound (US) demonstrated significantly lower levels of weight loss 18.62 ± 1.14 % and decay incidence 65.63 ± 3.9 %, respectively. However, the antioxidant activity of combined treated (HW+US) banana fruits was considerably higher after treatments (p ≤ 0.05). The same treatment delayed the changes ash content, ascorbic acid, firmness, color content and demonstrated the greatest suppression of microbial growth, with values ranging from 1.09 ± 0.09 to 5.15 ± 0.24 log10 cfu/g for total plate count (TPC) and 0.9 ± 0.11 to 5.01 ± 0.16 log10 cfu/g for total yeast mold count (TYMC), during the 0th to 12th days of storage that contributed to the banana's prolonged shelf life. Based on the findings, combined hot water and ultrasound treatment (HW+US) can be considered promising postharvest treatment of bananas, could extend their shelf life, minimize microbial contamination, and enhance overall quality retention during ambient storage. Further refining of the imitations is recommended to optimize treatment conditions, which might evaluate the efficiency of HW+US on other perishable fruits and assess its scalability for commercial applications, hence contributing to waste reduction and enhanced marketability.